Loading of the Manufacturing Systems Elements in the Process of Unsteady Mode Cutting and the Models of their Arrangement Deviations; Applied Mechanics and Materials; Vol. 682 : Innovation Technology and Economics in Engineering - Putilova U. S. (Material Science, Machining Technologies and Equipments in Mechanical Engineering, 2014)
Title screen